Using the Strain Index and TLV for HAL to Predict Incidence of Aggregate Distal Upper Extremity Disorders in a Prospective Cohort - (:unkn) unknown (My University, 2012)
Work-related distal upper extremity (DUE) musculoskeletal disorders (MSDs) are very prevalent and costly in the United States. It is important to recognize working conditions that lead to these disorders, in order to lessen the impact that they have on workers and their employers. Identifying jobs that are likely to cause DUE MSDs is difficult because there are many factors that are believed to contribute to DUE MSD development. The current study aims to determine if the Strain Index (SI) and the ACGIH TLV for HAL (two DUE job physical exposure assessment methods) predict increased risk of workers developing aggregate DUE MSDs. For this study, aggregate disorders include: (i) carpal tunnel syndrome, (ii) lateral epicondylitis, (iii) medial epicondylitis, (iv) tendonitis of wrist flexors and extensors, (v) de Quervain's disease, and (vi) trigger finger. Subjects for this study were drawn from a recently completed large-scale prospective cohort study consisting of 1,205 volunteer workers from 21manufacturing companies located in IL, UT, and WI. Of the 1,205 workers, only those workers who had no previous history of an aggregate disorder at study onset will be considered. Workers were followed monthly to determine if new DUE MSD symptoms developed. Specific case definitions are used to identify when a worker develops one or more aggregate DUE MSD. Physical exposures from workers' jobs were individually measured and videos were recorded at baseline. Jobs were investigated quarterly to determine physical exposure changes and re-analyzed as necessary. Time to first aggregate DUE MSD was modeled using proportional hazards regression to determine if there is a relationship between SI and TLV for HAL scores and increased risk of developing DUE MSDs while controlling for relevant covariates (age, gender, BMI). Univariate analyses, showed a strong relationship between age (HR = 1.03, p = 0.001) and gender (HR = 2.38, p = 0.002) and the development of aggregate DUE MSDs. There was suggestive evidence that the SI, with a cut point of 6.1 (p = 0.13), predicts increased risk of first lifetime aggregate DUE MSD. No significance was noted for the TLV for HAL. Efforts per minute showed a slightly significant association using a spline placed at 37.3 (p = 0.03). Multivariate analyses found suggestive evidence for an association between efforts per minute when analyzing using a spline placed at 37.3 efforts per minute (p = 0.08). No effect was found with the SI or TLV for HAL. Age and gender appear to be significantly associated with the development of first lifetime DUE MSD. The SI appears to be a more reliable method to use to determine jobs that place workers at increased risk of developing first lifetime aggregate DUE MSD, when comparing it to the TLV for HAL.
Keywords: Distal Upper Extremity; Musculoskeletal Disorders; Strain Index; TLV for HAL